Factor out the 3:
3(x^2+3x+2)
Unfoil:
3(x+1)(x+2)
Take the roots:
x=-1 or -2
2006-11-18 12:32:10
·
answer #1
·
answered by banan 2
·
1⤊
1⤋
This is a classic case of having trouble factorising quadratic polynomials. People have had problems with this in the past. Maybe you should see 'similar questions' before wasting 5 points. Anyway, here's the answer:
3x^2+9x+6
The easieast way to factorise this is to split the middle term, that is '9x' into two terms. In order to get the two apprpriate terms needed, follow these steps:
1. Multiply the coefficient of the first term with the last term. (3*6 = 18)
2. Factorise the product (18)
18 = 1*18
2*9
3*6
3. Pick out two factors that add up to make the coefficient of the middle term. (3 + 6 = 9)
4.Split the middle term (9x = 6x + 3x)
Now let's get on with the factorisation:
3x^2+9x+6 = 3x^2 + 6x + 3x + 6
= 3x(x + 2) + 3(x + 2)
= (3x + 3)(x + 2)
2006-11-18 13:00:20
·
answer #2
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
1⤋
I assume you mean factor, you didn't say
3x^2+9x+6
3(x^2+3x+2)
3(x+2)(x+1)
2006-11-18 14:32:11
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
I'm assuming it's = 0 but even if it isn't the factorization is still correct.
3(x^2 + 3x +2) = 0
3(x+1)(x+2)=0
thus x = -1 or x = -2
2006-11-18 12:46:13
·
answer #4
·
answered by Insomniac 1
·
0⤊
1⤋
3x^+2+9x+6
Group like terms, we get
3x^+9x+2+6
9x+9x+2+6
Adding like term, we get
18x+8
ans = 18x+8
2006-11-18 12:51:35
·
answer #5
·
answered by Jay 2
·
0⤊
1⤋
90
2006-11-18 12:37:43
·
answer #6
·
answered by Christine 4
·
0⤊
2⤋
One can but I think it may be assigned to you. So the question is ' can you solve this problem.'
2006-11-18 12:45:27
·
answer #7
·
answered by BILL 6
·
0⤊
1⤋
what am i supposed to solve for? thats just a function
2006-11-18 12:30:58
·
answer #8
·
answered by sprinter/jumper40 1
·
2⤊
1⤋
My dad said the first x shouldn't be there.
2006-11-18 12:41:05
·
answer #9
·
answered by Jenny Yin 2
·
1⤊
1⤋